Development of a high-speed power line communication system - Tang, Loon Tiong. (2008)
This thesis aims to analyze the characteristics of power lines in Singapore power distribution network in order to develop a channel model suitable to stimulate its behaviours for high-speed data transmission. The characteristics of interest to power line communications (PLC) are noise, signal attenuation, phase shift caused by the power line to the transmitted signal, and the impedance of the power line as seen by the PLC transmitter and receiver.